Effect of Buserelin on superovulatory response in cattle - RAWAT, A K; KUMAR, SURESH; SAXENA, M S; MAURYA, S N; SINGH, VIJAY (The Indian Journal of Animal Reproduction, 2007)
The present study was conducted to evaluate the effect of administration ofbuserelin acetate at superovulatory estrus, on superovulation and embryo recovery in bovine embryo transfer programme. A total of37 donor animals were divided into control (C, n=I 9) and experimental (E, n=l8) groups. At the superovulatory estrus, donor animals of group C were injected with 5ml normal saline solution while animals in group E received 21 mg of buserlin acetate, by IM route. Superovulatory response was measured in terms of mean ovulation rate, anovulatory follicles, viable embryos and total ova/ embryos recovered. The findings of the present study indicate that there was no significant effect of inclusion ofbuserlin acetate in superovulatory regimen.